The position of supervisor (Al-Nadhir) and its inheritance by the scholarly families in Damascus during the centuries (7-9 AH / 13-15 AD) - Awad, Riad Salim; Shabeeb, Taha Ibrahim (Research Journal in Advanced Humanities, 2025)
Damascus city was characterized by a distinctive feature that was focused on by historical sources that dealt with the history of administrative organizations in it, which is the feature of inheriting administrative positions by men from the scientific families that were famous at that time, and the most important position that these families inherited was the position of supervisor (inspector), and the phenomenon of inheriting administrative positions by scientific families reflected a set of historical facts about the features of the administrative system in Damascus, including: that the family has a fundamental role in supporting administrative life, and that the ruling authority at that time agreed to the continuation of this phenomenon - functional inheritance - among those scientific families because it was confident that the correct tool for evaluating the administrative apparatus in the country is the scholar who is a descendant of these ancient families, in other words, the ancient and honorable history that the family possessed was a reason for the authority to choose its scholars to assume the positions of financial management at that time.